Integrating Electrical and Structural Cardiac Adaptations in Professional Basketball Players to Enhance Training Efficiency and Recovery - Dewa Ayu Made Sriartha Kusuma Dewi; Arga Setyo Adji; Setya Haksama; Alan Dharmasaputra; Angela Puspita; Bambang Edi Suwito; Jordan Steven Widjaja; Atiyatum Billah (Postgraduate, University of Mataram, 2026)
Professional basketball players undergo high-intensity training that promotes cardiac adaptations. This literature review summarizes current evidence on electrical and structural cardiac remodeling in professional basketball players and explores implications for training and recovery. Structural changes, such as ventricular enlargement and atrial remodeling, are common in this population. Early repolarization patterns are frequently observed, reflecting advanced physiological adaptation rather than isolated abnormalities. Integrating cardiovascular screening with performance and recovery monitoring can help optimize individualized training strategies, improve recovery, and maintain athlete health. This synthesis provides practical insights for sports medicine professionals and coaches to enhance player performance while minimizing cardiac risk.